2018
DOI: 10.1186/s12877-018-0751-1
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluations of non-pharmacological interventions for persons with dementia and their informal caregivers: a systematic review

Abstract: BackgroundThis systematic review aims to review the literature on trial-based economic evaluations of non-pharmacological interventions directly targeted at persons with dementia as well as persons with mild cognitive impairment and their respective caregivers.MethodsA systematic literature research was conducted for the timeframe from 2010 to 2016 in the following databases: Centre for Reviews and Dissemination, EconLit, Embase, Cochrane Library, PsycINFO and PubMed. Study quality was assessed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
(104 reference statements)
0
49
0
4
Order By: Relevance
“…Additionally, total spending on home care for Medicare beneficiaries with Alzheimer's or other dementias nearly doubled between 2004 and 2011, although increases in spending may be due to a variety of factors, including more people being diagnosed with Alzheimer's dementia, more people using home care, an increase in the number of coexisting medical conditions, more intensive use of home care services and an increase in Medicaid coverage by older adults 207,549 . In two recent systematic reviews of the cost‐effectiveness of home support interventions for individuals with dementia, researchers found some evidence to support occupational therapy, home‐based exercise and some psychological and behavioral treatments as potentially cost‐effective approaches, although the research that has evaluated both the costs and benefits of home support interventions is scant 550,551 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, total spending on home care for Medicare beneficiaries with Alzheimer's or other dementias nearly doubled between 2004 and 2011, although increases in spending may be due to a variety of factors, including more people being diagnosed with Alzheimer's dementia, more people using home care, an increase in the number of coexisting medical conditions, more intensive use of home care services and an increase in Medicaid coverage by older adults 207,549 . In two recent systematic reviews of the cost‐effectiveness of home support interventions for individuals with dementia, researchers found some evidence to support occupational therapy, home‐based exercise and some psychological and behavioral treatments as potentially cost‐effective approaches, although the research that has evaluated both the costs and benefits of home support interventions is scant 550,551 …”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…207,549 In two recent systematic reviews of the cost-effectiveness of home support interventions for individuals with dementia, researchers found some evidence to support occupational therapy, home-based exercise and some psychological and behavioral treatments as potentially cost-effective approaches, although the research that has evaluated both the costs and benefits of home support interventions is scant. 550,551 Transitions between care settings Individuals with dementia often move between a nursing facility, hospital and home, rather than remaining solely in a nursing facility. In a longitudinal study of primary care patients with dementia, researchers found that individuals discharged from a nursing facility were nearly equally as likely to be discharged home (39%) as discharged to a hospital (44%).…”
Section: Use and Costs Of Long-term Care Servicesmentioning
confidence: 99%
“…Possible explanations for the inconsistencies can be the focus on different outcome parameters, sample sizes, or intervention periods. Additionally, many studies have adopted the narrower perspective of the health care and social system, instead of the comprehensive societal perspective [30]. Moreover, generalizability is restricted on account of different health care systems in other countries [30].…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…Major strengths of our study are the randomized design and the relatively large sample size in comparison to former studies with similar designs [30,70,74].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation